2017
DOI: 10.1080/09658211.2017.1296164
|View full text |Cite
|
Sign up to set email alerts
|

Memory skills mediating superior memory in a world-class memorist

Abstract: Laboratory studies have investigated how individuals with normal memory spans attained digit spans over 80 digits after hundreds of hours of practice. Experimental analyses of their memory skills suggested that their attained memory spans were constrained by the encoding time, for the time needed will increase if the length of digit sequences to be memorised becomes longer. These constraints seemed to be violated by a world-class memorist, Feng Wang (FW), who won the World Memory Championship by recalling 300 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…This demonstrates that procedural knowledge about what it means to recall in serial order also contributes to memory span. Other evidence comes from studies demonstrating that within a domain of expertise, substantially more information can be retained than is widely assumed to be within the capacity of WM (Ericsson, 2014;Ericsson et al, 2017; see chapter by Hambrick, Burgoyne, and Araújo, 2020). Some of the best known findings have arisen from studies of expert chess players who can retain details of multiple chess positions based on storage in LTM (e.g.…”
Section: The Role Of Ltm Knowledge In Wm Storage and Processingmentioning
confidence: 99%
“…This demonstrates that procedural knowledge about what it means to recall in serial order also contributes to memory span. Other evidence comes from studies demonstrating that within a domain of expertise, substantially more information can be retained than is widely assumed to be within the capacity of WM (Ericsson, 2014;Ericsson et al, 2017; see chapter by Hambrick, Burgoyne, and Araújo, 2020). Some of the best known findings have arisen from studies of expert chess players who can retain details of multiple chess positions based on storage in LTM (e.g.…”
Section: The Role Of Ltm Knowledge In Wm Storage and Processingmentioning
confidence: 99%
“…For example, the sequence 984 could be remembered as 9.84 s, or a record time for running 100 m. He became very proficient at translating number sequences into running times, etc., allowing him, after several weeks of intensive training, eventually to dramatically increase his memory span for digits, but this was specific to digits. More recently, and even more dramatically, Ericsson et al (2017) have reported a range of memory strategies used by world memory champion Feng Wang who achieved recall of 300 random digits presented at one per second.…”
Section: Expertise Mattersmentioning
confidence: 99%
“…An intriguing memory technique known for millennia, the memory palace or method of loci [127][128][129][130] , is widely exploited by memory athletes in mnemonic competitions 131,132 . Given a list of typically non-spatial items to memorize, such as a sequence of playing cards, memory athletes imagine walking along a specific path through a familiar and richly remembered space, such as one's childhood home or school, Fig.…”
Section: Mechanism For the Methods Of Loci (Memory Palace) Techniquementioning
confidence: 99%